Studying the impact of built environments on human mental health in everyday life: methodological developments, state-of-the-art and technological frontiers - Reichert, Markus; Lautenbach, Sven; Zipf, Alexander (Current opinion in psychology, 2020)
Rapid worldwide urbanization benefits humans in many aspects, but the prevalence of common psychiatric disorders is increased in urban populations. While the impact of city living and urban upbringing on mental health is well established, it remains elusive which of the multiple factors of urban living convey risk and resilience for mental disorders. For example, air pollutants, traffic noises and fragmented social networks are some of the highly interdependent and complex influences of city living suggested to be detrimental for mental health. In contrast, urban green spaces, social contacts and physical activity have been associated with increased well-being. Knowledge on underlying mechanisms of these associations is crucial for both city planning and healthcare as it informs on how to build environments and to intervene in a way that fosters mental health yet reduces psychiatric disorders. Thus, real-life studies in urban contexts have been launched making use of recent methodological advancements: Mobile devices (e.g. smartphones) to gather intensive longitudinal mental health data, stationary sensor output providing specific context information (e.g. on weather conditions and air pollution), combinations with traditional and modern neuroimaging techniques (e.g. functional near-infrared spectroscopy and portable magnetic-encephalogram caps) and modern virtual reality setups allowing for increasingly realistic and ecological valid simulation of complex urban environments. Here we review selected methodological developments, state-of-the-art approaches as well as technological frontiers and provide examples for their application, highlighting promising potential of these novel methods for tackling the urgent urbanicity societal issue of the 21st century with a view to improve urban contexts conducive to mental health.